Thymic stromal lymphopoietin-activated basophil promotes lung inflammation in mouse atopic march model - Xu Li; Zizhuo Li; Mindan Tang; Kaoyuan Zhang; Kaoyuan Zhang; Kaoyuan Zhang; Ting Yang; Weilong Zhong; Bo Yu; Bo Yu; Bo Yu; Fang Wang; et al. (Frontiers in Immunology)
BackgroundAtopic dermatitis (AD), a prevalent inflammatory skin disease affecting 10%-20% of the population, is linked to the development of asthma through atopic march (AM). This study aims to explore the role of basophils in OVA-induced lung inflammation in the presence of AD-like skin lesions and investigate the potential contribution of thymic stromal lymphopoietin (TSLP) in activating basophils.MethodsMouse AM models were established in C57BL/6 mice using MC903 and OVA epicutaneous sensitization, followed by intranasal OVA challenges. An intraperitoneal OVA-sensitized asthma model was employed as the control group. RNA-Seq analysis was conducted on lung CD45+ immune cells from these models. Histologic examinations, flow cytometry, and ELISA were used to examine the lung and systemic inflammatory response. Basophil depletion was achieved through intraperitoneal administration of anti-FcϵRIα mAb. The role of TSLP was investigated using TSLPR knockout mice.ResultsAs in the intraperitoneal sensitization model, AM model also induced eosinophilic lung inflammation in mice, resembling the AM process. The RNA-Seq analysis revealed differential gene expression, with genes related to basophils being prominent in AM model. Increased basophil activation and IL-4 production were observed in OVA epicutaneously sensitized mice. Basophil depletion attenuated the eosinophilic lung inflammation. TSLP levels increased with topical MC903, and TSLPR knockout reduced lung inflammation, suggesting TSLP is involved in basophil activation.ConclusionBasophils play a crucial role in OVA-induced lung inflammation in the context of AD-like skin lesions, and TSLP appears to drive basophil activation. Understanding these interactions provides insights for potential therapeutic interventions in AM-associated conditions.